Breeding of a new lychee cultivar Guishuang - LIN Jinhe; LI Hua; GU Yingjun; GU Xingfu; YE Hanjiang; LIU Guanyi (Guoshu xuebao)
Guishuang is a late-maturing, yield-stable, and high-quality lychee cultivar selected and bred from a mutant seedling of lychee in Daguang Village, Zhenglong Township, Huiyang District, Huizhou Municipality. The mother tree is currently about 50 years old. In the early spring of 1999, more than 40 scion sticks from the lychee mother trees were collected and grafted onto 23 Huai Zhi lychee seedlings in the orchard at a low position. A total of 46 buds were grafted and 41 were survived. Starting from 2003, all the 23 grafted lychee trees (first generation trees) bloomed and bore fruit. The average fruit weight is 31.7g, with a crooked heart shape. The flesh is crisp and fiber-free, and has a osmanthus fragrance. The flesh eatability rate is 78.7%, and the skin is dark red. The soluble solids content is 17.1%-18.6%, and the seed abortion rate is 86.7%. The tree vigor is robust. Leaves are short, with a symmetrically aristate tip, and a lanceolate shape. The crown is semi-circular, and open. The leaf veins are fine with entire leaf margin and smooth and glossy surface. The flowers are small, born on a compound raceme and cone-shaped inflorescence, light yellow green in color, and neatly arranged. The pedicle is brown and round. The fruit matures in mid July. The cultivar has prominent characteristics such as large size, high and stable yield, easy flowering and excellent quality. The yield per plant for top-grafted trees reached 17.3 kg in the fourth year and 24.3 kg in the fifth year. Propagration can be carried out through techniques such as air layering, grafting, and top grafting. For grafting, Feizixiao can be used as the rootstock, while Guiwei or Feizixiao can be used for top grafting. The orchard can be established on slopes with a gradient below 25 degrees. It is advisable to dig a planting hole with a depth of 1 meter and a diameter of 0.8 meters for new seedlings, with sufficient base fertilizer. Spring planting is recommended; Planting density can be (4-5) m × (5-6) m; Benign weeds or green manure can be planted between rows to improve and enhance the ecological environment in the orchard, which is conducive to improving fruit quality. Guishuang usually has its last autumn shoots maturing at the end of November to early December. After the autumn shoots mature, spiral girdling can be carried out to control the shoots and promote flowering. If winter shoots sprout, 0.03%-0.04% ethephon solution can be sprayed before the winter shoots bloom. 3-5 and 20-25 days after the female bloom, fruit retention can be achieved by spraying the nutrient agent containing 2, 4-D+ “Sheng Duo Su”. After the second physiological fruit drop period, the fruit can be appropriately thinned out, retaining 5 to 9 fruits per cluster. Plant protection measures should be focused on preventing and controlling two pests and two diseases, including lychee stink bug, stem end borer, downy mildew, and anthracnose. It is suitable for mid-to late-maturing lychee producing areas in Guangdong and Guangxi.